Non Quasi-Static Model of DG Junctionless FETs - Mohammad Bavir; Abdollah Abbasi; Ali Asghar Orouji; Farzan Jazaeri; Jean-Michel Sallese (IEEE Journal of the Electron Devices Society)
In this paper an analytical non-quasi-static (NQS) model for long-channel symmetric double-gate junctionless field-effect transistors (JLFETs) operating in depletion mode is proposed for the first time. The model addresses the limitations of existing DC and AC models by incorporating time-dependent current continuity equations which are essentials to predict JLFETs behavior at high frequencies. Leveraging charge-based equations, the NQS model captures the delay between current and applied potentials arising beyond the quasi-static regime. Analytical solutions for small-signal perturbations allow the calculation of key transistor small signal parameters such as the gate transadmittance. The model’s validity is tested against TCAD simulations for various device parameters, including doping concentration and channel thickness. Good agreement between the model and TCAD simulations is observed across a wide frequency range, up to highly non-static transport conditions. This work lays the foundation for a comprehensive RF model of JLFETs for high-frequency applications.